2022
DOI: 10.3390/healthcare10030409
|View full text |Cite
|
Sign up to set email alerts
|

‘Analogy-Based Comprehensive Diabetes Education’ (ABCDE) Improves Glycemic Control of Diabetic Patients in an Underserved Population: Results of a Retrospective Chart Analysis

Abstract: Diabetes is the leading global cause for blindness, kidney failure and amputations. Preventing these complications requires optimal glycemic control, and it is imperative that diabetic patients understand the fundamental concepts of diabetes care. Although patients attend formal diabetes education classes, many do not comprehend basic concepts of diabetes, and are often noncompliant with diet, exercise and medications. A novel approach termed ‘analogy-based comprehensive diabetes education’ (ABCDE) was develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Under Japan's universal public health insurance system, a five-year follow-up of local disease management programs, including patient education programs with a focus on preventing diabetic complications, showed that these programs were somewhat effective in reducing diabetic complications and the need for emergency care [ 27 ]. In a retrospective chart review conducted in the United States and published in 2022, the effects of comprehensive diabetes education on the reduction of glycated hemoglobin (HbA1c) and fasting blood glucose were reported [ 8 ]. This initiative included explanations of the importance of diet, exercise, medication use, annual eye examinations, hyperglycemia, and HbA1c testing [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under Japan's universal public health insurance system, a five-year follow-up of local disease management programs, including patient education programs with a focus on preventing diabetic complications, showed that these programs were somewhat effective in reducing diabetic complications and the need for emergency care [ 27 ]. In a retrospective chart review conducted in the United States and published in 2022, the effects of comprehensive diabetes education on the reduction of glycated hemoglobin (HbA1c) and fasting blood glucose were reported [ 8 ]. This initiative included explanations of the importance of diet, exercise, medication use, annual eye examinations, hyperglycemia, and HbA1c testing [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective chart review conducted in the United States and published in 2022, the effects of comprehensive diabetes education on the reduction of glycated hemoglobin (HbA1c) and fasting blood glucose were reported [ 8 ]. This initiative included explanations of the importance of diet, exercise, medication use, annual eye examinations, hyperglycemia, and HbA1c testing [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation